Modern Management and Diagnosis of Hypertension in the United Kingdom: Home Care and Self-care - James P. Sheppard; Claire L. Schwartz; Katherine L. Tucker; Richard J. McManus (Ubiquity Press, 2016)
Background The effective diagnosis and management of hypertension is one of the most important parts of cardiovascular prevention internationally and this is no different in the United Kingdom. Approximately 14% of the UK population currently receive treatment for hypertension. Recent UK guidelines from the National Institute of Health and Care Excellence have placed greater emphasis on the utilization of out-of-office measurement of blood pressure to more accurately diagnose hypertension. Objective The aim of the present study was to provide a state-of-the-art review of the evidence for screening, diagnosing, and managing hypertension, as implemented in the United Kingdom, with an emphasis on the role of self-monitored and ambulatory blood pressure monitoring in routine clinical care. Method Consideration was given to the use of ambulatory and home monitoring to confirm a diagnosis of hypertension and the use of self-monitoring and self-management to monitor and guide treatment. The evidence for the use of self-monitoring in patients with hypertension was examined, both in isolation, and in combination with lifestyle and treatment interventions. Findings There is a place for self-monitored blood pressure in specific underresearched populations such as the elderly, specialist conditions, ethnic groups, and during pregnancy and this is discussed here. Conclusions The evidence supporting the use of out-of-office monitoring in all aspects of routine clinical care has increased substantially in recent years and is reflected in increased utilization by patients and clinicians alike. Several areas require further research but it is clear that out-of-office monitoring is here to stay and is fast becoming an important part of hypertension management in the United Kingdom.